Deformation and fracture of Titanium and Aluminium alloys - Chew, Kia Guan. (2008)
The aim of the research was to study the deformation and fracture of titanium alloy Ti-6A1-4V and aluminium alloy 6061 in ambient environment subjected to low impact and loading range. The method of approach has been to carry out tension, impact and fatigue tests on the two materials and some of their welded joints. In contrast to the titanium alloy Ti-6A1-4V, strength of the aluminium alloy 6061 was shown to be insensitive to strain rate (0.1-1000 mm/min) in ambient environment. The effect of material orientation is also insignificant in the aluminium alloy 6061 under quasi-static loading. The rate of fatigue crack growth in the aluminium alloy 6061 is insensitive to frequency (1-35 Hz) at room temperature, but fatigue resistance was measured to be higher when crack propagation is in the T-S direction than in the L-S direction. Microscopic observations revealed banding in the microstructure which helped to improve the fatigue resistance.